Growth in VLBW infants fed predominantly fortified maternal and donor human milk diets: a retrospective cohort study - Colaizy Tarah T; Carlson Susan; Saftlas Audrey F; Morriss Jr Frank H (BMC, 2012)
Abstract Background To determine the effect of human milk, maternal and donor, on in-hospital growth of very low birthweight (VLBW) infants. We performed a retrospective cohort study comparing in-hospital growth in VLBW infants by proportion of human milk diet, including subgroup analysis by maternal or donor milk type. Primary outcome was change in weight z-score from birth to hospital discharge. Methods Retrospective cohort study. Results 171 infants with median gestational age 27 weeks (IQR 25.4, 28.9) and median birthweight 899 g (IQR 724, 1064) were included. 97% of infants received human milk, 51% received > 75% of all enteral intake as human milk. 16% of infants were small-for-gestational age (SGA, < 10th percentile) at birth, and 34% of infants were SGA at discharge. Infants fed >75% human milk had a greater negative change in weight z-score from birth to discharge compared to infants receiving < 75% (−0.6 vs, -0.4, p = 0.03). Protein and caloric supplementation beyond standard human milk fortifier was related to human milk intake (p = 0.04). Among infants receiving > 75% human milk, there was no significant difference in change in weight z-score by milk type (donor −0.84, maternal −0.56, mixed −0.45, p = 0.54). Infants receiving >75% donor milk had higher rates of SGA status at discharge than those fed maternal or mixed milk (56% vs. 35% (maternal), 21% (mixed), p = 0.08). Conclusions VLBW infants can grow appropriately when fed predominantly fortified human milk. However, VLBW infants fed >75% human milk are at greater risk of poor growth than those fed less human milk. This risk may be highest in those fed predominantly donor human milk.